Synthesis, Antibacterial, and Antifungal Activities of Novel Pyridazino Carbazoles. (18th December 2012) - Yaqub, Ghazala; Hannan, Abdul; Akbar, Erum; Usman, Muhammad; Hamid, Almas; Sadiq, Zubi; Iqbal, Mehwish
Abstract : Strategy to synthesize novel carbazole, that is, 2, 3-dihydro-2-phenyl-6 H -pyridazino[4, 5- b ]carbazole-1, 4-dione (2 ), is developed as key reaction. This novel compound showed ideal reactivity toward different functional groups like methyl, carboxylic, nitro, piperazine, and amine; thus series of its derivatives are synthesized sequentially with the aim to fuel up the carbazole compounds with new versatile derivatives. All compounds were investigated for their activity against bacteria (MRSA and S. typhi ) and fungi ( Candida albicans ). Among tested compounds 3, 6, and 8 exhibited pronounced antibacterial activities while 2, 5, and 9 also showed moderate activities. 2, 3, 5, 7, and 9 showed stronger antifungal activity against Candida albicans comparable to positive control.